2000
DOI: 10.1128/jb.182.9.2507-2512.2000
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for Na+Influx via the NtpJ Protein of the KtrII K+Uptake System inEnterococcus hirae

Abstract: The ntpJ gene, a cistron located at the tail end of the vacuolar-type Na ؉ -ATPase (ntp) operon of Enterococcus hirae, encodes a transporter of the KtrII K ؉ uptake system. We found that K ؉ accumulation in the ntpJdisrupted mutant JEM2 was markedly enhanced by addition of valinomycin at pH 10. Studies of the membrane potential (⌬⌿; inside negative) by 3,3-dihexyloxacarbocyanine iodide fluorescence revealed that the ⌬⌿ was hyperpolarized at pH 10 in JEM2; the ⌬⌿ values of the parent strain ATCC 9790 and JEM2, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
21
1

Year Published

2001
2001
2010
2010

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 44 publications
3
21
1
Order By: Relevance
“…The system from Synechocystis sp. PCC 6803 is the third Ktr system for which Na ϩ dependence has been established (26,27). Because at present no Na ϩ -independent Ktr system is known, Na ϩ dependence may be a general feature of Ktr systems.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The system from Synechocystis sp. PCC 6803 is the third Ktr system for which Na ϩ dependence has been established (26,27). Because at present no Na ϩ -independent Ktr system is known, Na ϩ dependence may be a general feature of Ktr systems.…”
mentioning
confidence: 99%
“…However, ntpJ from E. hirae has later been identified as a K ϩ -translocating subunit of the bacterial Ktr-type K ϩ uptake system (11, 21, 24 -27). Ktr from Vibrio alginolyticus is Na ϩ -dependent, and the same may apply to the Ktr system from E. hirae (26). KtrB belongs to a superfamily of K ϩ transporter proteins, with members in Archaea (KdpA, TrkH), bacteria (KdpA, TrkH, KtrB), fungi (TRK), and plants (HKT) (26 -38).…”
mentioning
confidence: 99%
“…Ktr is present in many bacteria (1, 29 -32) and appears to always require Na ϩ ions for activity (9,10,32). It is not known whether Na ϩ activates the K ϩ transport process (32) or whether Ktr functions as a K ϩ /Na ϩ symporter (10). VaKtr consists of two types of subunits.…”
mentioning
confidence: 99%
“…It belongs to the KTN (K ϩ transport, nucleotide binding) protein/domain family (PFAM2254/COG0569; GOLD genomes online database) (33) and has been proposed to regulate K ϩ transport via KtrB by a change in its binding from NAD ϩ to NADH according to a "ligand-mediated conformational switch" mechanism (33). The second subunit, the integral membrane protein VaKtrB (called NtpJ in Enterococcus hirae) (10,34), is responsible for K ϩ transport across the membrane (2,29). In this study, we mutated each of the four putative selectivity filter glycine residues in VaKtrB at positions 70, 185, 290, and 402 (see Fig.…”
mentioning
confidence: 99%
“…Considering the orientation of the genes and the presence of putative terminators, the phenotypes of these four mutants could not be linked to a polar effect of the mutation on downstream genes. This was not the case for sal5, in which the transposon was inserted into lmo0992, a gene of unknown function located upstream from lmo0991 which encodes a protein with similarities to NtpJ of Enterococcus hirae, a K ϩ /Na ϩ transporter (16). In these five mutants, similarity searches could not assign a putative function to the genes interrupted, but a search for transmembrane domains with the DAS program (5) revealed that FIG.…”
Section: Resultsmentioning
confidence: 99%